Incidence of Acute and Chronic Post-Thoracotomy Pain in Pediatric Patients - Giuliano Marchetti; Alessandro Vittori; Fabio Ferrari; Elisa Francia; Ilaria Mascilini; Emiliano Petrucci; Simone Piga; Valerio Pardi; Marco Cascella; Giorgia Contini; Franco Marinangeli; Alessandro Inserra; et al. (MDPI AG, 2021)
We studied acute and chronic pain in pediatric patients who underwent thoracotomy for benign disease with a follow-up of at least three months. A telephone interview investigated about the presence of pain and the analgesic therapy in progress. The results were compared with the anesthetic technique, postoperative pain and the adequacy of pain therapy, both during the first week after surgery and at the time of interview. Fifty-six families consented to the study. The mean age of the children at surgery was 2.9 ± 4.5 years, while at the time of the interview was 6.5 ± 4.4 years. We performed different anesthetic strategies: Group A: general anesthesia (36 pts); Group B: general anesthesia and thoracic epidural (10 pts); Group C: general anesthesia and intercostal nerve block (10 pts). During the immediate postoperative period, 21 patients (37.5%) had at least one painful episode. At the time of interview, 3 children (5.3%) had moderate chronic neuropathic (burning) pain on surgical scar. There was no statistically significant difference between the type of anesthesia and the incidence and severity of acute post-operative pain. Despite its limitations, this study confirms the low incidence of chronic post-thoracotomy pain syndrome in children.